Viabilitas dan Vigor Benih Serta Perbedaan Karakter Vegetatif Plasma Nutfah Padi Lokal Aceh dengan Varietas Padi Unggul Nasional - yuliana, yuliana; Irawan, Jekki; Maulidia, Vina (Jurnal Agrotek Lestari, 2025)
Aceh as one of the provinces rich in local rice variety diversity is part of the wealth of germplasm in Indonesia. In the West-South Aceh (Barsela) region, local rice that is very diverse is still widely cultivated by farmers. Local rice has advantages that are useful for improving rice varieties in the future. This research was conducted at the Experimental Garden of the Faculty of Agriculture, Teuku Umar University. The materials used in this study were local Aceh rice germplasm seeds of the Siputeh, Jantong, Tinggong and Sigupai varieties, the introduction of IRBB-27, superior varieties Inpari 32 and, manure, inorganic fertilizers, and the soil used was top soil. While the tools used in this study were buckets, hoes, watering cans, digital cameras, labels, markers/pencils, rollers and observation books, scoops, rulers, analytical scales, and wood. Varieties affect the viability and vigor of rice seeds, the best results were found in the treatment of local Aceh Tinggong rice germplasm. The height growth of local, introduced and superior national rice plants varies greatly between one variety and another. The highest rice plant is the local rice germplasm of Aceh Siputeh, while the largest number of tillers is in the local rice germplasm of Aceh Tinggong. These genotypes can be used as genetic sources for the assembly of new superior varieties.Keywords: Aceh local rice, genetics, plant breeding